Ferroelectrically tunable magnetic skyrmions in ultrathin oxide heterostructures. Issue 12 (December 2018) - Wang, Lingfei; Feng, Qiyuan; Kim, Yoonkoo; Kim, Rokyeon; Lee, Ki; Pollard, Shawn; Shin, Yeong; Zhou, Haibiao; Peng, Wei; Lee, Daesu; Meng, Wenjie; Yang, Hyunsoo; et al.
Abstract Magnetic skyrmions are topologically protected whirling spin texture. Their nanoscale dimensions, topologically protected stability and solitonic nature, together are promising for future spintronics applications. To translate these compelling features into practical spintronic devices, a key challenge lies in achieving effective control of skyrmion properties, such as size, density and thermodynamic stability. Here, we report the discovery of ferroelectrically tunable skyrmions in ultrathin BaTiO3 /SrRuO3 bilayer heterostructures. The ferroelectric proximity effect at the BaTiO3 /SrRuO3 heterointerface triggers a sizeable Dzyaloshinskii–Moriya interaction, thus stabilizing robust skyrmions with diameters less than a hundred nanometres. Moreover, by manipulating the ferroelectric polarization of the BaTiO3 layer, we achieve local, switchable and nonvolatile control of both skyrmion density and thermodynamic stability. This ferroelectrically tunable skyrmion system can simultaneously enhance the integratability and addressability of skyrmion-based functional devices. Ferroelectric control of skyrmion density and stability is realized in a perovskite heterostructure.